Cluster-Based MSE Development: The Role of Kaizen Training (The Pakistan Development Review, 2015)
It has been increasingly recognized that entrepreneurship holds the key to industrial development in developing countries [World Bank (2012)]. Indeed, a significant number of studies find that productivity and profitability vary greatly across enterprises even in the same industry in the same country, and that a large part of the variation can be accounted for by the difference in management practices1Identifying and supporting high-potential entrepreneurs may be the key to the success of industrial development. Entrepreneurship is the capacity to introduce new ideas into practice and to manage enterprise operations efficiently. Innovation here does not necessarily mean scientific discovery or engineering invention but the Schumpeterian creation of a new combination of production resources and new ideas to increase profits. In the context of developing economies, innovation includes borrowing technology or learning from abroad. The first introduction of products and production processes from developed countries into a developing country and the first adoption of management practices that may be common in developed countries but are novel in developing countries are considered to be innovations.